Pengaruh Penggunaan Cairan Rempah Pada Pembuatan Roti Soft Roll Terhadap Daya Terima Konsumen - Clarisa Naftali; Cucu Cahyana; Guspri Devi Artanti (Universitas Negeri Medan, 2021)
This study aims to analyze the effect of using spices in making soft roll bread on consumer acceptance. The research was conducted at the Pastry & Bakery Laboratory of Cuninary Education Program, State University of Jakarta. The sample in this study was a soft roll bread with the use of 50%, 75%, and 100% liquid spices. Assessment of consumer acceptance was carried out by organoleptic tests of 30 untrained panelists, namely the community around the house. The assessment of consumer acceptance was carried out by using the Friedman test with a significant level of α 0.05. Based on the results of the hypotheses, there was an effect of the use of spices on the aspects of volume, aroma, and taste, but there were no differences in the aspects of skin color, burning rate, crust, skin, pores, tissue texture, and chewing quality. Based on the results of the tuckey test, it shows that the soft roll bread with the use of spices at a percentage of 75% is the recommended formula.